Community pharmacists as catalysts for deprescribing: An exploratory study using quality improvement processes. (January 2020) - Farrell, Barbara; Clarkin, Chantalle; Conklin, James; Dolovich, Lisa; Irving, Hannah; McCarthy, Lisa; Raman-Wilms, Lalitha
Background: There is growing international emphasis on deprescribing, involving the monitored reduction or stopping of medications that are no longer needed or that cause more harm than benefits, especially for the elderly. Community pharmacists are well positioned to partner with patients and their other health care providers in facilitating deprescribing activities. Objective: To build community pharmacists' capacity to integrate deprescribing into their daily practices through training and workflow strategies. Methods: This study used an exploratory mixed-methods (primarily qualitative) design. Staff at 4 Ontario pharmacies were trained to use deprescribing guidelines. Qualitative data were collected through field observations, notes from advisory group meetings and documented Plan-Do-Study-Act (PDSA) plans. Quantitative data were derived from process and output measures reported by the pharmacies. Iterative PDSA cycles allowed the project team to appraise and accelerate process improvements over time and to summarize findings on facilitators, barriers and the adaptation of processes. Results: All 4 pharmacies identified individual and common goals related to deprescribing; however, drugs targeted and use of professional services to identify and address deprescribing opportunities varied. Each demonstrated that deprescribing activities could be integrated into daily practice and workflow. Common themes characterized approaches taken by each pharmacy: (1) processes used for capacity building among staff to identify patients for possible deprescribing, (2) approaches for preliminary interactions with patients, (3) in-depth medication reviews and (4) follow-up and monitoring. Approaches changed over time. Conclusion: Deprescribing appears to be feasible in community pharmacies. Data derived to populate a business model canvas informs the development of an in-depth business model for deprescribing. Can Pharm J (Ott) 2019;152:xx-xx.